Building your first trading partner community a competitive edge down the road. - Bushey, Scott (SOA webservices journal.)
Web services seem like a great way to tackle the challenge of trading partner integration. In theory, participants can continue to use the enterprise applications they prefer and expose them to their partners' systems.